The African World Congress for paediatric and congenital heart disease - Hugo-Hamman, Christopher (SA Heart Journal, 2017)
Cape Town presents a sublime and compelling African destination for the 6th World Congress of Paediatric Cardiology and Cardiac Surgery. The South African Heart Association (SA Heart) is host and the Paediatric Cardiac Society of South Africa the organiser of this important and historic international event. The World Congress is also the annual meeting of SA Heart. We welcome delegates to our city, our country and the African continent.